Swedish Dissertations and their Subjects, 1600-1820 (Volume One) : An Annotated Catalogue - Kärrholm, Mattias (Early Modern History and Modern History E-Books Online, Collection 2024, 2024)
This book challenges earlier understandings of early modern dissertations as unimaginative academic exercises. It argues for their continuous importance in scholarly and scientific discourse, and describes the richness and diversity of their subjects and themes. The book contains a complete catalogue of the almost 20,000 Swedish dissertations defended in Uppsala, Lund and Åbo, 1600 to 1820. The catalogue includes longer comments and descriptions of a few thousand of these dissertations, and also gives an analysis of how different subjects have evolved over time.